Basigin genetic depletion reduces thoracic aortic aneurysm formation in marfan syndrome mice. (14th October 2021) - Rurali, E; Vodret, S; Perrucci, G L; Falsone, F; Serri, P; Trabelsi, E; Zacchigna, S; Pompilio, G
Abstract: Background: Marfan Syndrome (MFS) is a rare genetic disease due to mutations in fibrillin 1 gene [1]. It is characterized by thoracic aortic aneurysm (TAA), whose dissection is the major cause of morbidity and mortality in MFS patients [2]. While pathological mechanisms underlying MFS extracellular matrix remodelling have started to be elucidated, an etiological treatment is not available yet [3, 4]. Recently, EMMPRIN has been proposed as new actor in pro-fibrotic processes associated with TAA development in MFS patients [4, 5]. Purpose: To confirm the role of EMMPRIN (i.e. Basigin in mice, Bsg) in TAA formation and progression in a preclinical setting, we assessed whether Bsg genetic depletion in a mouse model of MFS (Fbn1C1039G/+) [6] had an impact on aortic phenotype. Methods: We generated a double transgenic mouse model, Fbn1C1039G/+-Bsg+/−, by crossing commercially available Fbn1C1039G/+ with Bsg+/− mice (provided by Dr. Kadomatsu) [7] and we prospectively measured aortic root size in 12 Fbn1C1039G/+-Bsg+/−, 9 Fbn1C1039G/+, and 15 WT mice every 4 weeks from 12 to 20 weeks of age by 2D-echocardiography. Both qRT-PCR and Western Blot were used to evaluate EMMPRIN downstream pro-fibrotic pathway activation in thoracic aortic tissue obtained from mice sacrificed at 12 weeks. Plasma soluble EMMPRIN (sEMMPRIN) levels were assessed by ELISA. Results: Echocardiographic assessment at 12 and 20 weeks of age confirmed significantly dilated aortic root in Fbn1C1039G/+ vs WT (mean±SD at 12 weeks: 1.772±0.081 vs 1.394±0.068 mm, respectively, p<0.0001; 20 weeks: 1.899±0.103 vs 1.520±0.083 mm, respectively, p<0.0001), and revealed that Fbn1C1039G/+-Bsg+/− mice had lower aortic root diameter extent compared to Fbn1C1039G/+ (12 weeks: 1.667±0.109 vs 1.772±0.081 mm, respectively, p=0.026; 20 weeks: 1.752±0.129 vs 1.899±0.103 mm, respectively, p=0.011). Pro-fibrotic gene profiling in a subset of 12 weeks old mice showed that Col1A1, Col3A1 and FN1 genes were more expressed in Fbn1C1039G/+ than in WT mice and that the up-regulation of these genes was mitigated in Fbn1C1039G/+ by Bsg depletion (ANOVA p=0.048, p=0.055, and p=0.0003, respectively). Moreover, we found a significant activation of the EMMPRIN downstream pro-fibrotic ERK1/2 pathway in Fbn1C1039G/+ compared to WT mice which was attenuated in the Fbn1C1039G/+-Bsg+/− model (p=0.030). Plasma sEMMPRIN levels were lower in Fbn1C1039G/+ than in WT mice, consistent with what we previously observed in MFS patients [5], and decreased over time in both Fbn1C1039G/+ and WT mice (2-way ANOVA disease p=0.013, time p=0.012, interaction p=ns). Conclusions: Basigin genetic depletion reduces dilatation of the aortic root and pro-fibrotic pathway activation in a preclinical MFS model, confirming previous proof-of-concept findings and paving the way for the development of innovative therapies for MFS patients. Plasma sEMMPRIN levels stand as promising tool to predict the aortic enlargement progression in MFS models and patients. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Italian Ministery of Health